Dynamics of Volunteering and Life Satisfaction in Midlife and Old Age: Findings from 12 European Countries - Thomas Hansen; Marja Aartsen; Britt Slagsvold; Christian Deindl (2018)
A growing literature shows that doing voluntary work not only helps the wider community but can also improve one’s own well-being. To date, however, few studies have examined the relationship between volunteering and well-being in non-US and especially in comparative data. We study this relationship using two waves of data of 18,559 individuals aged 50 and above from 12 European countries. We analyze life satisfaction impacts of change and stability in volunteering status and in the intensity (frequency) of volunteering, and explore whether these impacts differ according to life stage (age, employment status) and across countries with different norms and supports for voluntarism. Findings show that net life satisfaction is higher among longer-term, recent, and former volunteers than among stable (long-term) non-volunteers. There are no significant life satisfaction differences between the three groups with volunteer experience. Equally, similar levels of life satisfaction are observed among people who have increased and decreased their frequency of volunteering. It thus seems to be the experience and not the dynamics (i.e., change or persistence) of volunteering that is associated with well-being. Findings further suggest life course variation in the association between volunteering and well-being, as the relationship is stronger for older and long-term non-employed (mostly retired) individuals than for their middle-aged and working counterparts. The relationship is also stronger in countries where volunteering is less common and less institutionally supported.